Continuous Co–P coating on CNTs by optimising electrodeposition. (1st February 2017) - Liang, J.; Li, H.; Shi, X.; Qi, L.; Hu, X.; Wei, J.
Abstract : Continuous Co2 P nanoparticles were deposited on the surfaces of carbon nanotubes (CNTs) with the thickness of 7–10 nm by electroless plating. Effects of pH, temperature and plating time on the coating were discussed and the optimised processing parameters were obtained. The morphologies and components of Co2 P–CNTs nanocomposites were analysed by TEM and energy dispersive spectroscope. The results indicated that Co2 P nanoparticles were deposited on multi-walled carbon nanotubes homogeneously at the temperature of 45°C, pH of 4.9 and plating time of 30 min. The saturation magnetisation of uniform Co2 P–CNTs nanocomposites was 2.81 emu g –1 and the coercivity was as high as 1285.2 Oe. Compared to those of the bulk cobalt, the coercivity of Co2 P–CNTs nanocomposites was enhanced while the saturation magnetisation decreased.